Interpretasi Makna Ahl Al- Kitab dalam Pandangan Alquran - Habieb Bullah (JURNAL ILMU AL-QUR'AN DAN TAFSIR NURUL ISLAM SUMENEP, 2021)
The Qur'an is like a spring, from which abundant water flows. All benefit from the water. The scholars from the past until now have taken from the Qur'an various fields of scientific disciplines. Fiqh experts take the essence of the laws derived from the Qur'an and then apply them to Muslims. Likewise with linguists who make the Qur'an the main literature in the field of language. Everything that comes from the Qur'an which includes law, examples (amthal), stories of the past people, advice, wisdom and others can be taken and used. All Islamic teachings in principle have been contained in this holy book. Its contents are very universal in accordance with the times and food. As a guide, its existence needs to be lived, pondered and absorbed information or noble values ​​in it. Because, the truth of the instructions is guaranteed by Allah SWT. However, to get a proper understanding is not like understanding a book or other books. For this reason, certain relevant methods or disciplines are needed, so that what is contained in the Qur'an can be absorbed properly. The scholars then took advantage of the Qur'an so that it could be studied for the next generation. As well as the meaning of ahl al-kitab contained in the Qur'an. This study uses a descriptive-analytic method which includes an analysis of the meaning of ahl al-kitab in the Qur'an. Thus, this research produces a critical view regarding the interpretation of the ahl al-kitab in the Qur'an.